A spectrum of scaly rashes. Issue 1 (12th January 2011) - Lio, Peter A
Abstract : Dermatophile has a new format. From now on, it will take the form of a short quiz to test and inform your knowledge of dermatology relevant to paediatrics. Any suggestions for improvement or topics you would like to be covered are welcome. Please email comments and feedback to p-lio@northwestern.edu . Answers to the following quiz questions can be found on page 39.